Analysis of a magnetic gear integrated Halbach generator. Issue 6 (7th November 2016) - da Costa Neves, Carlos Guilherme; Flores Filho, Aly Ferreira
Abstract : Purpose: The purpose of this paper is to simulate a magnetic gear full integrated generator (MGFIG) to apply in wind power generation. Design/methodology/approach: A 2D finite element model of the MGFIG was built. The static magnetic torque on air-gaps was obtained by Maxwell stress tensor. In order to simulate the movement of both rotors in relation to the winding and modulators two movement bands were applied. Findings: It was proved that the MGFIG magnetized with Halbach arrays is able to eliminate the cogging torque, improve the quality of the generated voltage waveform and decrease the core losses and permanent magnet eddy current losses. Practical implications: The loss coefficients belonging to core material were found from the measured curves provided by an electrical manufacturer. Originality/value: The originality of this paper is to improve the good characteristics of a MGFIG, such as a simple mechanical structure, good utilization of permanents magnet (PM) materials and lower manufacturing cost, by incorporating Halbach PMs arrays to decrease core and eddy current losses, improve the voltage waveform.